An unlikely union : the love-hate story of New York's Irish and Italians - Moses, Paul (Professor of English) (New York University Press, 2015)
"An Unlikely Union unfolds the dramatic story of how two of America's largest ethnic groups learned to love and laugh with each other in the wake of decades of animosity. The vibrant cast of characters features saints such as Mother Frances X. Cabrini, who stood up to the Irish American archbishop of New York when he tried to send her back to Italy, and sinners like Al Capone, who left his Irish wife home the night he shot it out with Brooklyn's Irish mob. Also highlighted are the love affair between radical labor organizers Elizabeth Gurley Flynn and Carlo Tresca; Italian American gangster Paul Kelly's alliance with Tammany's "Big Tim" Sullivan; hero detective Joseph Petrosino's struggle to be accepted in the Irish-run NYPD; and Frank Sinatra's competition with Bing Crosby to be the country's top male vocalist. In this engaging history of the Irish and Italians, veteran New York City journalist and professor Paul Moses offers an archetypal American story. At a time of renewed fear of immigrants, it demonstrates that Americans are able to absorb tremendous social change and conflict--and come out the better for it."--Publisher's description